Airbus SE : equity valuation - Carmo, Henrique António Costa da Silva (2019)
This dissertation performs an estimation of the fair value of Airbus SE’s common stock to verify whether the share price is fairly priced. The Discounted Cash Flow (DCF) model, the relative valuation and the dividend discount model were the three methodologies chosen to estimate the firm’s fair value. The multiples estimated were the P/E, EV/EBITDA and the EV/Revenues. The valuation results are then compared with an equity report published by UBS. The DCF model approach, applied to Airbus SE, yielded a price per share of €125.42 which resulted in a HOLD recommendation. This recommendation is only driven by the DCF method, since the prices obtained by the relative valuation differ across the different multiples. The DCF valuation takes into account the future perspectives for the industry and the strategy followed by Airbus SE in the last five years which will influence the future. Esta dissertação pretende estimar o justo-valor de cada acção da Airbus SE e verificar se o preço actual está adequado.